ANALISIS HUKUM TERHADAP INVESTOR INSTITUSIONAL SEBAGAI SALAH SATU PENENTU FAKTA MATERIL DALAM PRINSIP KETERBUKAAN DI PASAR MODAL - Efendi Tambunan; Bismar Nasution; Sunarmi Sunarmi; Mahmul Siregar (Universitas Sumatera Utara, 2014)
ABSTRACT Capital market is one part of the financial market, that are important for national development in general , especially for the development of the business as an alternative source of external financing by company. The stock market will always have ups and downs , as indicated by the signs of bullish or bearish , which is influenced by information or material facts. There are three principles that must be adhered to in the capital market , namely disclosure ( transparency ) , fairness ( honesty ) , investors protection. The results of the study led to the conclusion that material information under the Capital Market Law are, first, information or relevant facts regarding the events. Second , the fact that can affect the price of securities and or decisions of investors. Other conclusion is information about the entry of institutional investors to trade in the stock market is a material fact , because it can affect the price (which is reflected in the rise and fall of Composite Index) , and also affects other investors to trade . Key words : Investor Institutional , Material Fact, Principle of Transparency